Pembentukan Karakter Religius Melalui Pembelajaran Integratif Berbasis Pesantren di MTS Negeri 1 Pasuruan - Abdul Khakim; Muhammad Anas Ma’arif (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This research analyzes efforts to form students' religious character through Islamic boarding school-based integrative learning at Madrasah Tsanawiyah Negeri 1 Pasuruan. Religious character is an important aspect in Islamic education which is not only related to understanding religion, but also behavior and moral values that are in accordance with Islamic teachings. This study uses a qualitative approach with data collection methods through observation, interviews, and document analysis. The research subjects involved students and teachers at MTs Negeri 1 Pasuruan. The research results show that Islamic boarding school-based integrative learning can play an important role in shaping students' religious character. Islamic boarding schools as a model of traditional Islamic education provide a supportive environment for religious learning and religious practices. Students who take part in this learning show an increased understanding of religion, strong moral values, and commitment to implementing Islamic teachings in everyday life. In addition, teachers play a central role in the process of forming religious character by providing the necessary guidelines, guidance and role models